Preliminary guidelines for a requirements-based approach to certification by simulation for rotorcraft - van’t Hoff, Stefan; Lu, Linghai; Padfield, Gareth D.; Podzus, Philipp; White, Mark D.; Quaranta, Giuseppe (Cranfield University, 2022)
The paper presents an introduction to the preliminary guidelines for rotorcraft certification by simulation developed by the partners of the Clean Sky 2 project Rotorcraft Certification by Simulation – RoCS . The guidelines are primarily aimed at the application of (rotorcraft) flight modelling and simulation in support of certification for compliance with standards CS-27 and CS-29, PART B (Flight) and other Flight-related aspects (e.g. CS-29, Appendix B, Airworthiness Criteria for Helicopter Instrument Flight). However, the guidelines are also applicable, in principle, to the certification of other types of rotorcraft, including tilt-rotors and e-VTOL configurations. A requirements-based approach is advocated and outlined, acknowledging the profound importance of assembling preliminary requirements, as complete as possible, before embarking on simulation development processes. The proposed approach presents examples of metrics for quantifying the fidelity that is ‘sufficient’ for application to relevant Applicable Certification Requirements (ACRs). The concept of ‘adaptive fidelity’ is introduced in this Guidance to emphasise that what might be sufficient is task-specific, and therefore ACR-specific. The paper introduces the structure of the proposed Rotorcraft Certification by Simulation process, together with the main concepts that guide applicants to the development of simulations that can be effectively employed to reduce the cost, timescales, complexity and risks that may be associated with certification performed solely though flight tests.